Treatment of bone loss in osteopenic patients with Crohn's disease: a double-blind, randomised trial of oral risedronate 35 mg once weekly or placebo, concomitant with calcium and vitamin D supplementation. Issue 9 (21st October 2013) - van Bodegraven, Ad A; Bravenboer, Nathalie; Witte, Birgit I; Dijkstra, Gerard; van der Woude, C Janneke; Stokkers, Pieter C M; Russel, Maurice G; Oldenburg, Bas; Pierik, Marieke; Roos, Jan C; van Hogezand, Ruud A; Dik, Vincent K; et al.
Abstract : Objective: Osteoporosis and fractures are frequently encountered in patients with Crohn's disease. In order to prevent fractures, treatment with bone protecting drugs appears warranted early in the course of bone disease when bone loss is not yet prominent. We therefore aimed to demonstrate a beneficial effect on bone density of the bisphosphonate risedronate in osteopenic Crohn's disease patients. Methods: This double-blind, placebo-controlled randomised trial of risedronate with calcium and vitamin D supplementation was performed in osteopenic Crohn's disease patients. Patients were treated for 2 years with follow-up after 3 and after every 6 months. Disease characteristics and activity and bone turnover markers were assessed at all visits; dual x-ray absorptiometry was performed at baseline, 12 and 24 months; radiographs of the spine at baseline and 24 months. Results: Of 132 consenting patients, 131 were randomised (67 placebo and 64 risedronate). Patient characteristics were similar in both groups, although the risedronate group was slightly heavier (body mass index 24.3 vs 23.0 kg/m 2 ). Bone mineral density at lumbar spine increased 0.04 g/cm 2 on average in the risedronate group versus 0.01 g/cm 2 in the placebo group (p=0.007). The mean increase in total hip bone mineral density was 0.03 versus 0.01 g/cm 2, respectively (p=0.071). Fracture prevalence and incidence were similar. Change of T-scores and concentrations of bone turnover markers were consistent with a beneficial effect of risedronate when compared with placebo. The effect of risedronate was primarily demonstrated in the first 12 months of treatment. No serious unexpected suspected adverse events were observed. Conclusions: A 24-month treatment course with risedronate 35 mg once weekly, concomitant with calcium and vitamin D supplementation, in osteopenic Crohn's disease patients improved bone density at lumbar spine. NTR 163 Dutch Trial Register.